2012
DOI: 10.3109/13685538.2011.646343
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of HIV risk practices among unprotected sex-seeking older and younger men who have sex with other men

Abstract: Purpose: In recent years, much attention has been devoted to understanding the HIV risk behaviors of younger men who have sex with men (MSM). Recent data suggest that HIV is becoming an increasing problem for older adults, but little attention has been devoted to understanding their HIV risk behaviors or the factors that underlie their risk taking. This study provides a comparison of these issues among younger and older MSM. Methods: The data come from a subset of younger (ages 18–39, n = 113) and older (age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 61 publications
(61 reference statements)
2
15
0
Order By: Relevance
“…In this way, our data is in line with previous research in this area ( e.g. , Klein, 2012) that suggests that differential rates of sexual risk taking are not responsible for increased HIV prevalence among YBMSM. However, YBMSM and OBMSM each had unique factors associated with their sexual risk taking behavior.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this way, our data is in line with previous research in this area ( e.g. , Klein, 2012) that suggests that differential rates of sexual risk taking are not responsible for increased HIV prevalence among YBMSM. However, YBMSM and OBMSM each had unique factors associated with their sexual risk taking behavior.…”
Section: Discussionsupporting
confidence: 92%
“…The results of previous studies do point to comparable rates of sexual risk taking, specifically condomless anal intercourse (CAI) among younger and older BMSM populations (Klein, 2012); however, little is known regarding whether the factors that contribute to HIV risk for the entire BMSM community accurately represent the HIV risks of younger BMSM in particular (Millett et al , 2012). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Age has also been shown to be associated with selfefficacy for condom use among people with substance use disorders in Taiwan, 16 among midlife and older women in San Diego, California, 10 and among MSM who seek sex partners from the internet in a national US study. 17 One study of Italian residents found that compared to adults aged 18-49, adults aged 60-75 reported lower scores on perceived behavioral control, the way in which individuals perceive their ability in condom use. 18 The association between age, and disclosure and selfefficacy may be explained by social cognitive theory.…”
mentioning
confidence: 99%
“…Lower levels of education, and thus knowledge, of sexually transmitted diseases (STDs) also affect an individual's sense of control over the disease. Much like their younger counterparts, older adults with a decreased understanding of the disease report lower self-efficacy in using condoms, as well as communicating with their partners about the disease and negotiating condom use (Klein, 2012). Studies report a lack of condom usage amongst older adults engaging in sexual contact with casual, non-monogamous partners (Rosenfeld, Bartlam, & Smith, 2012;Treas & Giesen, 2000).…”
Section: Introductionmentioning
confidence: 99%